The impact of environmental pollution on China's economic growth from the perspective of health damage - Li, Hao; Yang, Zihan; Chen, Jiahui (Frontiers in Public Health, 2025)
IntroductionAchieving an optimal economic growth rate is a cornerstone of high-quality development. Among the diverse factors influencing economic growth, environmental pollution and health-related issues have emerged as critical concerns in recent years.MethodsThis study develops a five-sector endogenous growth model that incorporates the effects of environmental pollution on health. The model theoretically examines the mechanisms through which environmental pollution and health jointly influence economic growth. Using panel data from 285 Chinese cities spanning 2002 to 2022, we empirically analyze the impact of environmental quality and health levels on economic growth, based on comprehensive measurements of these variables in Chinese urban areas.ResultsThe findings indicate that environmental quality and health are key drivers of economic growth. Specifically, environmental pollution not only directly hampers economic growth but also indirectly impedes it by degrading public health.DiscussionThese results underscore the importance of implementing robust environmental pollution control policies and improving public health standards. By reducing the adverse effects of environmental pollution on health, policymakers can mitigate the risk of environmental and health deterioration, thereby safeguarding China's pursuit of high-quality economic development.